Antigenic and structural characterization of Treponema pallidum (Nichols strain) endoflagella. - Blanco, D R (1988)
Purified endoflagella from Treponema pallidum, Nichols strain, were characterized both structurally and antigenically. Structural analysis showed T. pallidum endoflagella are composed of 35- and 33-kilodalton (kDa) subunits which lack cysteine and do not share N-terminal amino acid sequence homology (20 residues). Intact endoflagella were dissociated into the composite subunits by incubation, which disrupts noncovalent bonds. Antiserum raised against purified T. pallidum endoflagella identified shared epitopes on the endoflagellar polypeptides of the nonpathogen, Treponema phagedenis biotype Reiter. Pathogen-specific epitopes were also found on the 35- and 33-kDa polypeptides by using affinity-purified endoflagellar antibodies. The pathogen-specific epitopes were localized by immunoblotting analysis of chymotryptic digests of the endoflagellar subunits; 18- and 26-kDa fragments derived from the 35-kDa subunit were found to possess a majority of the pathogen-specific epitopes. Both the 35- and 33-kDa subunits had surface exposure, as determined by immunoelectron microscopy, although additional immunochemical data indicated that the surface exposure of the 35-kDa subunit was greater.